Dual effect of prostaglandin E2 on normal airways smooth muscle in vivo. Issue 12 (December 1982) - Walters, EH; Davies, BH
Abstract : Inhalation of prostaglandin E2 by normal subjects caused initial bronchoconstriction followed by the predominant effect of bronchodilatation, which was maximal by 15 minutes. The degree of bronchoconstriction seen in the early phase appeared to be related to the initial tone of airways smooth muscle and was exaggerated after bronchodilatation with a large dose of ipratropium bromide. Bronchoconstriction induced by prostaglandin E2 is a direct effect on muscle and not secondary to a vagal reflex initiated by airways irritant receptors.